A systematic study on the effects of doping agents on polypyrrole coating of fabrics. Issue 1 (24th September 2015) - Varesano, Alessio; Belluati, Andrea; Sanchez Ramirez, Diego Omar; Carletto, Riccardo Andrea; Vineis, Claudia; Tonetti, Cinzia; Bianchetto Songia, Michela; Mazzuchetti, Giorgio
ABSTRACT Polypyrrole is widely used as coating to produce electrically conductive textiles. Counter‐ions (i.e. doping agents) were embedded in polypyrrole to improve electrical conductivity. Good electrical performances are required for several applications, such as microwave attenuation/electro‐magnetic interference shielding, heat generation, electro‐static discharge protection, sensing, and energy storage. In this work, a systematic study was carried out on the effects of doping agents in coating cotton fabrics with a thin polypyrrole layer. A total of 11 compounds were selected and compared as counter‐ions. The electrical performances of the coated fabrics were assessed with measures of electrical conductivity. Moreover, evenness and morphology of the resulting polypyrrole layer were discussed. As the final result, the best performances in terms of electrical conductivity (i.e. low surface resistivity) were measured using on dicyclohexyl sulfosuccinate, 2, 6‐naphthalenedisulfonate or 1, 5‐naphthalenedisulfonate as doping agents. The weight increases after polypyrrole deposition on the fabrics were greater than 15% and polypyrrole deposited on the fibers as a uniform film. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 132, 42831.